The E-word on the public acceptance of experiments - Mira Fischer; Elisabeth Grewenig; Philipp Lergetporer; Katharina Werner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Randomized experiments are often viewed as the "gold standard" of scientific evidence but people's scepticism towards experiments has compromised their viability in the past. We study preferences for experimental policy evaluations in a representative survey in Germany (N>1,900). We find that a majority of 75% supports the idea of small-scale evaluations of policies before enacting them at a large scale. Experimentally varying whether the evaluations are explicitly described as "experiments" has a precisely estimated overall zero effect on public support. Our results indicate political leeway for experimental policy evaluation, a practice that is still uncommon in Germany.
Keywords: I28; H40; C93; 330; experiment aversion; policy experimentation; education